Description of the male of Acentrus boroveci Košťál, 2014 (Coleoptera: Curculionidae: Acentrusini) - Košťál, Michael; Košťálová, Zuzana (Zootaxa, 2016)
The male of the recently described Acentrus boroveci Košťál, 2014 is described for the first time, and characters to differentiate it from males of the two other species of Acentrus Desmarest, 1839 are given.
Keywords: Body Size; nosatcovití; Organ Size; velikost orgánu; velikost těla; mužské pohlaví; Weevils; ženské pohlaví; rozšíření zvířat; zvířata; Female; anatomické struktury zvířat; Animal Structures; Male; Animal Distribution; Animals